Study of the material processing within a drum of a washer-extractor - Alexander V. Maksimov, Larisa V. Sumzina (International Journal of Advanced Science and Technology, 2020)
The most important task for washer-extractors is to improve the design solutions of individual units and parts, which include a drum unit with ridges placed on it. It is relevant to conduct experimental studies of the influence of the main structural factors in drum washer-extractors on the intensification of material processing and improving the efficiency of their work cycle operations in order to modernize the existing designs of the working bodies. When developing and solving the problem of researching material processing processes, theoretical and experimental research methods were used, including the method of system-structural analysis and the method of mathematical planning of the experiment. The application of these methods allowed us to confirm the adequacy of the obtained regression model for the studied process. It has been established that an increase in the intensity of volumetric mixing of a material during its processing in the washing mode is achieved in drums with ridges having the form of helical surfaces. During rotation of the drum, the ridges of this shape give to the processed products additional movements along the axis of rotation of the drum and rotational movement relative to the centre of gravity. In turn, the increase in volumetric mixing of the processed material with such a shape of the drum ridges allows us to reduce the processing time required to obtain high values of the washing quality. Experimental studies were carried out to study the effectiveness of the use of helical drum ridges with applying the method of mathematical planning of the experiment. The beta coefficients are determined for various washing efficiency index values of the samples based on the well-known calculation methods and the developed computer program for calculating the coefficients. Verification of the adequacy of the regression equation using the Fisher test showed that the obtained regression model is adequate to the process under study with a confidence probability of 0.95.